Implementation of Cooperative Caching in Social Wireless Networks (International Journal of Engineering and Computer Science, 2017)
This paper introduced cooperative caching policies for minimizing the content provisioning cost in Social Wireless Networks(SWNET). SWNETs are formed by mobile devices, such as data enabled phones, electronic book readers etc., sharing common interest in electronic contents, and physically gathering together in public places. Electronic object caching in such SWNETs are shown to be able to reduce the content provisioning cost which depends heavily on the service and pricing dependences among various stakeholders including content providers (CP), network service providers, and End Consumers (ES). This Drawing motivation from Amazon’s Kindle electronic book delivery business, this paper develops practical network, service, and pricing models which are then used for creating two objects caching strategies for minimizing content provisioning costs in networks with homogeneous and heterogeneous objects demands. This paper constructs analytical and simulation models for analyzing the proposed caching strategies in the presence of selfish users that deviate from network-wide cost-optimal policies. It also report results from an Android phone-based prototype SWNET, validating the presented analytical and simulation results.